Exploring fungal antagonists: Diversity and biocontrol potential against grapevine (Vitis vinifera) foliar pathogens - A, MOUNIKA; C S, SHUKLA; C, CHANDRASHEKARA; S, SRIRAM (The Indian Journal of Agricultural Sciences, 2025)
Grapevine (Vitis vinifera L.) production is threatened by foliar pathogens like Alternaria, Colletotrichum, and Plasmopara leading to fungicide dependence, thereby raising concerns of residues and resistance. The present study was carried out during 2022–23 at ICAR-Indian Institute of Horticultural Research, Hesaraghatta, Karnataka to isolate and evaluate native fungal antagonists as sustainable biocontrol options. A hemi-biotrophic oomycete Phytophthora nicotianae was chosen as substitute for Plasmopara viticola. The in vitro co-culture studies of the isolated 42 fungal isolates with target pathogens identified 15 isolates showing mycelia growth inhibition of pathogens by and over 35%. Molecular characterization of these isolates using ITS-1F and 4R primers highlighted the constitution of opportunistic human pathogens (Mucor irregularis), mushrooms (Ganoderma spp. and Lentinula edodes), phytopathogens (Fusarium spp. and Pestalotiopsis spp.) and other fungi like Xylaria, Trichoderma, Nemania and Byssochlamys spp. Xylaria spp. (IIHR_BCF14) demonstrated efficacy comparable to T. harzianum (IIHR_BCF23), inhibiting the mycelial growth of all three target pathogens. Notably, Endomelanoconiopsis endophytica (IIHR_BCF20), Lntinula edodes (IIHR_BCF26), and Ganoderma species (IIHR_BCF38, IIHR_BCF40 and IIHR_BCF41) showed specific antifungal activity against A. alternata. The study signified the complexity associated with management of C. gloeosporioides with very few bioagents demonstrating antifungal activity against the pathogen. The study yielded few preliminary reports on directed antagonism of few biocontrol potent fungi (B. spectabilis, Xylaria spp. against P. nicotianae; E. endophytica against A. alternata) and emphasizes on their exploitation for management of grapevine pathogens.